Legal Protection of Tongkonan Traditional Areas Contained in the Cultural Reserve Area in Toraja - Nur, Sri Susyanti; Patittingi, Farida (International Journal of Psychosocial Rehabilitation, 2020)
The Cultural Heritage Area in the Tongkonan Kete Kesu area is an asset of North Toraja tourism which became the most receiving place for cultural tourists in 2017, so it was given the title "Most Popular Indigenous Village" at the 2017 Indonesian Charm Award event. Aluk Todolo culture, and the existence of traditional houses of Tongkonan, granary (alang), stone graves (liang) and graves in buildings (patane) have high cultural values that are still preserved in traditional life in the traditional area of Tongkonan Kete Kesu. The stipulation of Tongkonan Kete Kesu Customary Area as a Cultural Heritage Area and as a Tourism Industry Development Zone, in terms of the aspect of Agrarian / Land Law requires Legal Certainty and Legal Protection of Indigenous Peoples and Tongkonan Indigenous Areas that are in the Cultural Heritage Area.This research method is Empirical Law by looking at facts / legal phenomena that occur in practice and actual events in society. Research Result, that Tongkonan Kete Kesu Traditional Territory as a place for traditional / cultural life is based on the beliefs / cultural heritage of ancestors called aluk todolo or alukta. Also Conservation and maintenance of the environment of the Tongkonan Indigenous Area is an obligation for each member of the Indigenous Peoples based on the values of local wisdom and Utilization of the area of cultural heritage as a tourist attraction that brings economic value has not been synergized properly between the Provincial Government, Regional Government, related Agencies.